If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2n + 4) = 9(4n + 5) + 7 Reorder the terms: 7(4 + 2n) = 9(4n + 5) + 7 (4 * 7 + 2n * 7) = 9(4n + 5) + 7 (28 + 14n) = 9(4n + 5) + 7 Reorder the terms: 28 + 14n = 9(5 + 4n) + 7 28 + 14n = (5 * 9 + 4n * 9) + 7 28 + 14n = (45 + 36n) + 7 Reorder the terms: 28 + 14n = 45 + 7 + 36n Combine like terms: 45 + 7 = 52 28 + 14n = 52 + 36n Solving 28 + 14n = 52 + 36n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36n' to each side of the equation. 28 + 14n + -36n = 52 + 36n + -36n Combine like terms: 14n + -36n = -22n 28 + -22n = 52 + 36n + -36n Combine like terms: 36n + -36n = 0 28 + -22n = 52 + 0 28 + -22n = 52 Add '-28' to each side of the equation. 28 + -28 + -22n = 52 + -28 Combine like terms: 28 + -28 = 0 0 + -22n = 52 + -28 -22n = 52 + -28 Combine like terms: 52 + -28 = 24 -22n = 24 Divide each side by '-22'. n = -1.090909091 Simplifying n = -1.090909091
| 4d^2-2d=0 | | 4/5x=32 | | -3x+4=4x-17 | | 6(x-2)/9=4(x+1)/12 | | 7(x+1)+7=2x+5(3+x) | | -9+12x+13k-5x-2k-25= | | 5x-3=-3x+1 | | -19=5t | | -9(x-10)=17-8x | | 3x+(2*3x+5)=945 | | 6x-(7x+6)=4x-26 | | y=3.2x+0.7 | | 1.50x+2.00=20 | | 14=-7u | | 6y+2(y-9)=6(y+1)-3 | | x-5x-60-x-13=-17 | | 7(2n+5)=8(6n+1)+6 | | k(2k+2)-6(2k+4)=k(2k-4)+(6k+9) | | -30/6= | | x+12=2x+3+9(x-3) | | 3(x-4)-8=-5(-5x+2)-8x | | 15x+21=4(3x+6)+3x-3 | | 9+36/3^2 | | 5(x-3)=2(x+9) | | 3x-5=12x-18 | | 5(y+8)+y=3(y+4)-8 | | 8x+2=8(x-1) | | 2x-7(x+9)=11 | | 9(w+6)=-8w+3 | | (3x-1)(x+2)=20 | | 3(x-1)+5x-6= | | -2y-11=3y+9 |